Synthesis of Binary Complex Colloidal Particles by Using Polyelectrolyte Multilayer-Coated Particles as Templates - Koo, Hye Young; Lee, Ha-Jin; Kim, Jun Kyung; Choi, Won San (IOP PUBLISHING LTD, 2010)
We report a feasible fabrication of binary complex particles based on polyelectrolyte multilayer-coated particles (PEMPs). Binary complex particles were synthesized by combination of large organic and small inorganic nanoparticles. The PEMPs were prepared by alternating adsorption of two kinds of polyelectrolytes with opposite charges onto colloidal particles. In this structure, polyelectrolytes act as a matrix to bind precursor for metal nanoparticles. Following reduction and hydrolysis of the PEMPs could generate bimetallic complexes onto PEMPs. We found that size and composition of the bimetallic complexes depend on the amount of gold precursor added to the suspension of the PEMPs. (C) 2010 The Japan Society of Applied Physics
Keywords: NANOPARTICLES; NANOREACTORS; SILVER